Crossing Boundaries: VET, the Labour Market and Social Justice - Avis, James (International Journal for Research in Vocational Education and Training, 2018)
Purpose: The paper explores the relationship between vocational education and training (VET), the labour market and social justice in the current conjuncture. Approach: The paper adopts an approach rooted in critical policy analysis. It consequently sets the discussion within the wider socio-economic and political context. Such an approach enables an exploration of the changing nature of waged labour in current conditions. Results: A critical policy analysis facilitates a discussion of the labour process, waged labour and its intensification. At the same time these processes are allied to the effective expulsion and marginalisation of particular groups of workers from employment. Importantly, such processes need to be placed in their localised and spatial context within particular social formations. Conclusion: Equity models of social justice that emphasise equal opportunities, are restrictive and can be contrasted with equality models which have a more expansive and philosophically rooted understanding of justice. The paper through its examination of the salience of VET in the current conjuncture as well as its significance for a post austerity democratic and radical politics, argues for a relational analysis that seeks to interrupt the patterns of inequality precipitated by neo-liberalism.